2010
DOI: 10.1152/japplphysiol.01297.2009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between maximal lengthening and shortening contractions for biceps brachii muscle oxygenation and hemodynamics

Abstract: Eccentric contractions (ECC) require lower systemic oxygen (O2) and induce greater symptoms of muscle damage than concentric contractions (CON); however, it is not known if local muscle oxygenation is lower in ECC than CON during and following exercise. This study compared between ECC and CON for changes in biceps brachii muscle oxygenation [tissue oxygenation index (TOI)] and hemodynamics [total hemoglobin volume (tHb) = oxygenated-Hb + deoxygenated-Hb], determined by near-infrared spectroscopy over 10 sets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 36 publications
7
32
1
Order By: Relevance
“…DSmO 2 half-recovery time (DSmO 21/2RT ) is the time to reach 50 per cent of the difference between DSmO 2 at the end of the contraction phase and DSmO 2max in the recovery period; a faster DSmO 21/2RT is related to muscle oxidative capacity [8]. Mean decrease in DtHb (DtHb mean ) is the difference between the average DtHb value during the contraction phase and tHb baseline; greater decreases and relatively stable DtHb mean values during the contraction phase would indicate blood flow/O 2 supply occlusion owing to increased intramuscular pressure of the contraction [11]. Maximum increase in DtHb (DtHb max ) is the difference between the maximum DtHb value reached during the relaxation phase and tHb baseline; higher DtHb max values would indicate a greater increase in blood volume/flow [6].…”
Section: (B) New Methods and Signal Interpretabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…DSmO 2 half-recovery time (DSmO 21/2RT ) is the time to reach 50 per cent of the difference between DSmO 2 at the end of the contraction phase and DSmO 2max in the recovery period; a faster DSmO 21/2RT is related to muscle oxidative capacity [8]. Mean decrease in DtHb (DtHb mean ) is the difference between the average DtHb value during the contraction phase and tHb baseline; greater decreases and relatively stable DtHb mean values during the contraction phase would indicate blood flow/O 2 supply occlusion owing to increased intramuscular pressure of the contraction [11]. Maximum increase in DtHb (DtHb max ) is the difference between the maximum DtHb value reached during the relaxation phase and tHb baseline; higher DtHb max values would indicate a greater increase in blood volume/flow [6].…”
Section: (B) New Methods and Signal Interpretabilitymentioning
confidence: 99%
“…DSmO 2 desaturation time (DSmO 21/2DT ) is the time difference between contraction onset until DSmO 2 reaches 50 per cent of the difference value between SmO 2 baseline and DSmO 2 min ; a longer duration DSmO 21/2DT for a similar DSmO 2 min would represent a slower desaturation rate, indicating that O 2 demand is better matched by O 2 supply. DtHb mean is the difference between the average of the minimum DtHb amplitude reached during the 30 contractions and tHb baseline; a given DtHb mean value would indicate the level of blood volume or blood flow/O 2 supply over the exercise duration [11].…”
Section: (B) New Methods and Signal Interpretabilitymentioning
confidence: 99%
“…Using nearinfrared spectroscopy (NIRS), our previous study (23) showed that changes in biceps brachii oxygenation and hemodynamic values were smaller during maximal eccentric than concentric contractions of the elbow flexors. Since muscle force output was greater for eccentric than concentric contractions, the smaller changes in oxygenation/hemodynamic values were interpreted to represent lower muscle activation during maximal eccentric than concentric contractions.…”
mentioning
confidence: 99%
“…Thus it may be that muscle blood flow/oxygenation during eccentric exercise might be better maintained during the second bout compared with the first bout, thereby providing a better maintenance of oxidative energy metabolism during the second bout that results in less muscle damage. NIRS provides the information relating to muscle blood flow/oxygenation (23); however, no previous study has used NIRS to investigate the repeated-bout effect. It was expected that a combination of EMG and NIRS could provide a better picture of potential differences in muscle activation/oxygenation between the first (ECC1) and second eccentric exercise (ECC2) bouts and shed light on the underlying mechanisms of eccentric exercise-induced muscle damage and the repeated-bout effect.…”
mentioning
confidence: 99%
“…For example, DeFreitas et al reported a comparison of the two genders in the innervations zone (IZ) of the biceps muscle during isometric contraction 26) . Many researchers investigated EMG during eccentric and concentric contractions on BB muscle [27][28][29] . Merletti et al studied the variations in the surface EMG signal aiming to elucidate a method for determining muscle fatigue in the dominant biceps brachii muscle 30) .…”
Section: Discussionmentioning
confidence: 99%